The characteristics of profibrosis markers and endothelial dysfunctions in asthma patientswith obesity and diabetes mellitus type 2 - Yeryomenko, Galyna; Ospanova, Tetyana; Bezditko, Tetyana (ScienceRise: Medical Science, 2018)
The urgency of asthma (A) and comorbid pathologies such as diabetes mellitus type 2 (DM2) and obesity is doubtless in internal medicine. The aim. To study the effects of profibrotic mediators, endothelial dysfunction markers and homeostasis on the pulmonary and renal functions in patients with moderately severe and uncontrolled A. Materials and methods.The study involved 252 patients with: A – group І (n=62), A+DM2– group ІІ(n=105), A+obesity– group ІІІ(n=85). General clinical methods of examination were combined with assessments of the respiratory unction, loop flow volume, fasting blood glucose level, insulin level, НОМА-IR,МСР-1, ІL-8, ММР-9, endothelin-1(ЕТ-1), von Willebrand factor (VWF) and glomerular filtration rate (GFR). Results. Group II had the longest duration of the illness and the state of carbohydrate metabolism subcompensation. FEV1 in the groups: I = 64.0 [44.5;69.3] %, II = 51.0 [44.2;78.0] %, ІІІ = 57.0 [44.5;69.3] %; group III had the highest BMI. Groups II developed hyper glycaemia, II and III groups higher HOMA-IR and ET-1 concentration. All groups showed differently strong positive relationships between HOMA-IR and MCP-1. In group II, an excessive concentration of MCP-1 as the marker of fibrosis with progressing signs of a renal involvement was restrained by a proportional increase of fibrolysis indicator MMP-9 in favour of adaptive responses. A negative correlation with GFR and a positive one with albuminuria confirmed engagement of MCP-1 into tubulointerstitial damage processes. VWF was elevated in all patients and increasing with augmentation and severity of the course of A with comorbid states and involvement of vascular endothelium. Conclusions. A patients with comorbid states developed higher levels, versus isolated A and the controls, of MCP-1, ІL-8 and MMP-9 in blood, therewith revealing the participation of these molecular mediators in affection of the lungs and kidneys by the universal mechanism of formation of fibroplastic changes in the respiratory tract and tubulointerstitial fibrosis